Exploring the Relationship between Changes in Postpartum BCS (Body Condition Score) and Reproductive Performance in Dairy Herds - makki, meisam; Kamali, Sojdeh; Ahmadi, Mohammad Rahim (Journal of the Hellenic Veterinary Medical Society, 2022)
The current research aims to explore the effects of Body condition score (BCS) reduction on some reproductive factors such as re-pregnancy rate, number of inseminations per pregnancy, clinical endometritis, and ovarian activity in Holstein cows and also the effects of number of calving and its difficulty, on changes in the BCS. Data analysis with spss 21 software shows that with a further decrease in BCS first month after delivery, the percentage of non-pregnant cases in the herd and the number of cows with inactive ovaries increases significantly. The rate of endometritis significantly increases by increasing negative changes in BCS by 0.5 units or more. The number of inseminations necessary for creating pregnancy in two groups of decrease in BCS was different with a statistically significant difference. The odds ratios of developing clinical endometritis and also inactive ovaries in cows with BCS changes< 0.5 were significantly greater. In addition, odds ratios of pregnancy with finally 3 inseminations in cows with changes in BCS ≤ 0.5 were significantly different from cows with higher BCS changes. BCS changes of cows in second calving were not significantly different from cows in first calving, while the changes in calving 3 and 4 were significantly different. Easy parturition and parturition with some help was not different in BCS changes but dystocia but dystocia has been associated with significant BCs changes (P<0.05). According to these results, it can be concluded that a further reduction in BCS was associated with a reduction in the reproductive performance.